2021
DOI: 10.1038/s41598-021-95283-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the level of immunoglobulins and number of somatic cells as a factor shaping the immunomodulating properties of colostrum

Abstract: The aim of this study was to investigate the association between immunoglobulins and SCC as a factor in shaping the content of the immunostimulatory components of colostrum. Seventy-eight multiparous Polish Holstein–Friesian cows were selected for the experiment. Colostrum samples were collected immediately after calving (up to a max. of 2 h). The cows were divided into groups according to the following levels: Immunoglobulins (IG class)—(IG1) over 50 g/L, (IG2) up to 50 g/L; SCC class—(SCC1) up to 400 000/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Causes of CD4+ and CD8+ ratio dysregulation: it was found that T lymphocytes in the peripheral blood of OMG patients are impaired in regulation and are predominantly impaired in apoptosis of CD4+ T cells, and the dysregulation of CD4+ and CD8+ ratio may be related to this [31]. Due to impaired apoptosis of CD4+ T lymphocytes, activated self-reactive T cells cannot be cleared in a timely manner, and activated T cells cause B cells to proliferate by leaps and bounds, causing an overpowering immune response and the production of antibodies against autoantigens, which leads to the development of autoimmune diseases such as OMG [32].…”
Section: Discussionmentioning
confidence: 99%
“…Causes of CD4+ and CD8+ ratio dysregulation: it was found that T lymphocytes in the peripheral blood of OMG patients are impaired in regulation and are predominantly impaired in apoptosis of CD4+ T cells, and the dysregulation of CD4+ and CD8+ ratio may be related to this [31]. Due to impaired apoptosis of CD4+ T lymphocytes, activated self-reactive T cells cannot be cleared in a timely manner, and activated T cells cause B cells to proliferate by leaps and bounds, causing an overpowering immune response and the production of antibodies against autoantigens, which leads to the development of autoimmune diseases such as OMG [32].…”
Section: Discussionmentioning
confidence: 99%
“…In other domestic species, the mother's health status has been associated with the somatic cell count (SCC), which has been recognized as an indicator of milk quality [9]. The SCC is also an indicator of udder health and could in turn affect Igs secretion [9].…”
Section: Introductionmentioning
confidence: 99%
“…For dairy cows, in which colostrum and milk composition have seen more study in comparison to sows, the factors affecting the Igs concentration-the SCC and the colostrum composition-are essential for good health, calving season, breed, age, their production system, a healthy diet, length of non-lactating period, and the time delay between parturition and first milking [9]. Similar to cows, the composition of sow colostrum can be influenced by several factors, including those of the sow-independent variety, such as environmental conditions (including the temperature and quality of hygiene of the farm), the sow's diet, and sow-dependent factors including breed, parity, and general health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to propose a classification of colostrum quality based on IgG levels (Al-Majali et al 2007). The specific characteristics of the camel milk IgG described here, as well as their dynamic changes during postpartum, are crucial for understanding not only how the calf's immune system develops but also how camel milk and its bioactive components relate to human nutrition (Puppel et al 2021).…”
Section: Discussionmentioning
confidence: 99%